Processamento auditivo nas dificuldades de aprendizagem: um programa de intervenção terapêutica - Juchem, Luiza de Salles (2004)
The adequate processing of auditory information is an essential factor for an ideal school development. Many researches have pointed out this relation, although few suggested any type of intervention. Therefore, the present study aims to verify the efficiency of a multi-sensorial therapeutic program in a group of students with learning difficulties complaints and auditory processing disorders at SSW test. Fourteen nine-year-old children were selected. All of them were enrolled in the second grade of a state elementary school, whose teachers accused as having learning difficulties. The selection criteria of these children was: to have normal peripheral hearing (ISO-1999 -1990); timpanometry type A (JERGER, 1970); lack of phonetic and/or phonological disturbance and; presence of Gradual Memory Loss at the qualitative analysis of SSW test. The children were divided in two groups: A Therapy Group (TG), made up by four children, two boys and two girls, each gender with one low and one moderate score at the quantitative analysis of the SSW test, and a Non Therapy Group (NTG), made up by ten children, four girls and six boys, where there were three low, three moderate and four strong scores. The TG participated of an intervention program based on multi-sensorial activities divided in eighteen sessions of forty-five minutes each, twice a week, in a school classroom. One year after the initial evaluation, both groups were re-evaluated where the children of the TG achieved the normal standards at both qualitative and quantitative aspects of SSW test. On the NTG, two children achieved the normal standards on the qualitative analysis, four remained in the same level and four passed to a category of Phonemic Decoding. On the quantitative analysis, three presented normal standards, one low and six moderate. The results of the re-evaluation showed that both groups had their total scores increased at SSW test although no moderate level children of NTG achieved the normal score on the test unlike the children of the TG. Therefore, it can be concluded that the multi-sensorial therapeutic intervention program is efficient on the improvement of the auditory processing skills of children with learning difficulties complaints and with one type of auditory processing disorder, the Gradual Memory Loss.